Perbandingan Faktor-Faktor yang Menyebabkan Gangguan Pola Haid pada Remaja Putri di SMAN 1 Tasikmalaya - Neng Aneu Nurul Hidayah; Indri Budiarti; Ismet Muchtar Nur (Bandung Conference Series: Medical Science, 2022)
Abstract. Menstrual disorders are characterized by heavy or scanty bleeding, and prolonged or irregular menstruation. Signs of distress during menstruation are also influenced by biological factors such as hormonal disturbances and lifestyle, physical activity and nutritional status. The purpose of the study was to determine the relationship between lifestyle (diet & exercise) and BMI with menstrual pattern disorders in adolescents in Tasikmalaya City. The research method using cross sectional. The independent variables in this study were lifestyle (diet & exercise) and menstrual pattern disorders as the dependent variable. The sampling technique was purposive sampling, the number of samples was 74 people. Data analysis used Fisher exact test and logistic regression. The results showed that BMI with irregular menstrual patterns were mostly obese (86.5%) and those with regular menstrual patterns were mostly normal (75.7%); lifestyle eating patterns with irregular menstrual patterns are mostly unbalanced (64.9%) and mostly balanced on regular menstrual patterns (75.7%); the description of a sports lifestyle with irregular menstrual patterns and regular menstrual patterns, most of them exercise with 51.4% and 100%, respectively. Fisher exact statistical test results obtained that there is a relationship between lifestyle (diet and exercise) and BMI with menstrual pattern disorders with p value <0.05 (0.001<0.05; 0.000<0.05 and 0.000<0, 05). The results of the logistic regression test showed that there was a relationship between diet and BMI with menstrual pattern disorders (0.01<0.05 and 0.003<0.05), respectively, while exercise was not associated with menstrual pattern disorders (0.997>0.05). It was concluded that there was a significant relationship between lifestyle, namely diet, exercise and BMI with menstrual pattern disorders. Abstrak. Gangguan haid ditandai dengan perdarahan yang banyak atau sedikit, dan haid yang berkepanjangan atau tidak teratur. Tanda-tanda distres selama haid, ternyata juga dipengaruhi oleh faktor biologis seperti gangguan hormonal dan gaya hidup aktivitas fisik dan status gizi. Tujuan penelitian untuk mengetahui hubungan gaya hidup (pola makan & olah raga) dan BMI dengan gangguan pola haid pada remaja di Kota Tasikmalaya. Metode penelitian dengan menggunakan cross sectional. Variabel bebas dalam penelitian ini adalah gaya hidup (pola makan & olahraga) dan gangguan pola haid sebagai variabel terikat. Teknik sampling dengan cara Purposive sampling, jumlah sampel sebanyak 74 orang. Analisis data menggunakan uji fisher exact dan regresi logistic. Hasil penelitian menunjukkan bahwa BMI dengan pola haid tidak teratur sebagian besar obesitas (86,5%) dan pada pola haid teratur sebagian besar normal (75,7%); gaya hidup pola makan dengan pola haid tidak teratur sebagian besar tidak seimbang (64,9%) dan pada pola haid teratur sebagian besar seimbang (75,7%); gambaran gaya hidup olahraga dengan pola haid tidak teratur dan pada pola haid teratur sebagian besar berolahraga dengan masing-masing 51,4% dan 100%. Hasil uji statistik fisher exact diperoleh bahwa terdapat hubungan gaya hidup (pola makan dan olahraga) dan BMI dengan gangguan pola haid dengan masing-masing p value <0,05 (0,001<0,05; 0,000<0,05 dan 0,000<0,05). Hasil uji regresi logistik menunjukkan terdapat hubungan pola makan dan BMI dengan gangguan pola haid dengan masing-masing (0,01<0,05 dan 0,003<0,05), sedangkan olahraga tidak berhubungan gangguan pola haid (0.997>0,05).Disimpulkan bahwa terdapat hubungan yang bermakna antara dengan gaya hidup yaitu pola makan, olahraga dan BMI dengan gangguan pola haid.